Threats to cassava production: known and potential geographic distribution of four key biotic constraints - Herrera Campo, Beatriz Vanessa; Hyman, Glenn G.; Bellotti, Anthony C. (Springer, 2011)
Insect pests and plant diseases reduce cassava yields substantially, posing a threat to food security throughout the developing world. While agricultural scientists have recognized these threats, few assessments of the geographic distribution of cassava pests and diseases have been made at the global scale. The goal of this study is to make such an evaluation for four key biotic constraints to cassava production in developing countries: whiteflies, cassava green mites, cassava mosaic disease and cassava brown streak disease. Occurrence records were obtained from laboratory and biodiversity databases and from the scientific literature. These records were then used in ecological niche models to predict the potential distribution of cassava pests and diseases. The distribution maps were cross validated by holding back 20% of the occurrence records. Potential distribution maps were developed by combining the results of the best ecological niche models. Hotspots for potential cassava pest and disease outbreaks include the Mato Grosso in Brazil, northern South America, the African rift valley, the southern tip of India and much of Southeast Asia, where all four biotic constraints show high potential suitability. Our work highlights how potential geographical shifts in infestation hotspots for several cassava biotic constraints will require intensified monitoring, evaluation and research to prevent yield losses and ensure food security.